2008
DOI: 10.1111/j.1399-5448.2008.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Poorly controlled type 1 diabetes is associated with altered glutathione homeostasis in adolescents: apparent resistance toN-acetylcysteine supplementation

Abstract: Blood glutathione concentrations represent a measure of protection against oxidative damage. In earlier studies, we observed that, in adolescents with poorly controlled type 1 diabetes mellitus (T1DM), blood glutathione is significantly depleted because of increased rates of glutathione utilization. To determine whether increased availability of cysteine - one of the three constitutive amino acids of glutathione - would attenuate the alterations in glutathione metabolism, ten 16 +/- 1 yr-old adolescents with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…In our experiment, NAC supplementation in diabetic rats was not able to decrease the significant blood glucose and glycated hemoglobin levels [ Table 1] when compared to the diabetic/saline group, as has been shown in other studies on humans [18,28] and diabetic animals. [29] Possibly the destruction of pancreatic beta cells by alloxan-induced ROS generation [19] hindered the potentially therapeutic effect of NAC on these cells, and consequently on the hyperglycemia status.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In our experiment, NAC supplementation in diabetic rats was not able to decrease the significant blood glucose and glycated hemoglobin levels [ Table 1] when compared to the diabetic/saline group, as has been shown in other studies on humans [18,28] and diabetic animals. [29] Possibly the destruction of pancreatic beta cells by alloxan-induced ROS generation [19] hindered the potentially therapeutic effect of NAC on these cells, and consequently on the hyperglycemia status.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, poor conversion of NAC to cysteine, excess urinary NAC, and decreased uptake of plasma cysteine by red blood cells could be the cause for the lack of effect of NAC on the GSH levels in a diabetic state. [28] In other studies, diabetic rats treated with NAC showed lower levels of glycemia than untreated diabetic rats, but hyperglycemia is common to both groups of animals, in spite of the improvement in the GSH status after NAC supplementation. [13,35,40] Darmaun et al, [28] demonstrated high levels of blood glucose after NAC supplementation in diabetes type I, but erythrocyte GSH levels were still decreased, similar to our study [ Table 4].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Glutathione (GSH) plays an important role in a multitude of cellular processes and its deficiency is implicated in the etiology and progression of a number of human diseases including cardiovascular, immune, diseases of aging, and diabetes (1-7). GSH is a cofactor of many enzymes that are involved in the detoxification of oxygen radicals and the detoxification of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies report lower blood levels of LC and altered cysteine homeostasis (15,16) as well as lower H 2 S levels in diabetic patients (17,18). Along with a host of proteins, LC is a precursor of glutathione, which is considered essential for the reduction of cellular oxidative stress (19).…”
mentioning
confidence: 99%